Analysis Of The Effect Of Variation On Number Of Blades And Angles Of Attack On The Performance Of The Darrieus Water Turbine - Yulianto, Rendi (Sainteknol : Jurnal Sains dan Teknologi, 2020)
The development of water current technology is not too popular in Indonesia. This can be seen by the source of energy currently dominated by wind power which is using potential energy. If we look from point of view of climate dan geographic location, Indonesia have big potential to utilize water current technology. Performance of darrieus turbine are influenced by some factor, among them are number of blade and angle of attack. The variation used in this research are number of blades which is 3 blade and 4 blade and variations of angle of attack which is 0 and 10 . Also, water velocity at 0.81 m/s, 0.96 m/s, 0.99 m/s, and 1.07 m/s to see the impact given by each variation to performance of darrieus water turbine. The results show that the most optimum darrieus turbine with the highest power coefficient (Cp) is turbine with three blades and angle of attack 0 at current velocity 1.07 m/s. The changes of number of blades and angle of attack cause lift and drag force who work on blades also changes. With the right number of blades and angle of attack could give even more positive force which helps turbine to rotate. The more force that help turbine rotate the greater power being generated.